2018
DOI: 10.1103/physrevlett.120.227202
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Twisted Surface skyrmions in Bulk Crystals

Abstract: Magnetic skyrmions in noncentrosymmetric helimagnets with D_{n} symmetry are Bloch-type magnetization swirls with a helicity angle of ±90°. At the surface of helimagnetic thin films below a critical thickness, a twisted skyrmion state with an arbitrary helicity angle has been proposed; however, its direct experimental observation has remained elusive. Here, we show that circularly polarized resonant elastic x-ray scattering is able to unambiguously measure the helicity angle of surface skyrmions, providing dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 45 publications
5
85
1
Order By: Relevance
“…Similar phenomenon in three-dimensional multilayer magnetic system was reported theoretically [28] and experimentally [29][30][31]. In the structure called threedimensional skyrmion, Bloch-like skyrmions are in the middle of the film and Néel-like skyrmions are at the top and bottom surface of the film.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Similar phenomenon in three-dimensional multilayer magnetic system was reported theoretically [28] and experimentally [29][30][31]. In the structure called threedimensional skyrmion, Bloch-like skyrmions are in the middle of the film and Néel-like skyrmions are at the top and bottom surface of the film.…”
Section: Resultssupporting
confidence: 81%
“…In the structure called threedimensional skyrmion, Bloch-like skyrmions are in the middle of the film and Néel-like skyrmions are at the top and bottom surface of the film. This structure has been observed in Fe/Gd multiplayers [29], FeGe nanodisk [30], and bulk Cu2OSeO [31]. The composite only including top layer and bottom layer of the three-dimensional skyrmion is called Néel caps.…”
Section: Resultsmentioning
confidence: 79%
“…Our appeal to T&T scattering for an interpretation of the diffraction pattern produced by PTO/STO superlattices illuminated with circularly polarized photons mirrors previous work for crystalline materials. 31,32 B. Charge-quadrupole moment for Ti 4+…”
Section: A Preamble and Surveymentioning
confidence: 99%
“…We usually define the helicity of skyrmion by the phase χ [20] appearing in φ(ϕ) = N sk ϕ + χ, where the N sk is defined as the skyrmion number. In the recent year's studies [28,31], it is found that the skyrmion helicity can be decided by the combination of bulk and interfacial DMI. So the skyrmions with different DMI combinations, called by a joint name-the twisted(or hybrid) skyrmion, can have different helicities.…”
Section: Resultsmentioning
confidence: 99%